Motivational variables involved in commitment of female soccer players at different competitive levels - Dominguez-Escribano, M.; Ariza-Vargas, L.; Tabernero, C. (Soccer & Society, 2017)
Today more and more women are playing sport and choosing activities previously considered the exclusive domain of men, such as soccer. The main purpose of this study was to analyse the role of motivational variables (individual and team) regarding the commitment to and future expectations of playing higher levels of competition in a sample of female association soccer players (N = 117) at different levels of competition (local, regional and national leagues). Results confirm that the highest league shows high values in perception of success (ego orientation and task orientation), transactional psychological contract and future expectations. On the other hand, the local league produces high values in relational contracts. A path analysis tests a theoretical model with all the motivational variables as predictors of sporting commitment and future expectations. It shows the power of individual and team motivational variables in terms of predicting the involvement of women in soccer.